MO873: County-Level Characteristics Associated With Variation in End-Stage Kidney Disease Mortality in the United States, 2010–8. (3rd May 2022) - Snow, Kylie; Patzer, Rachel; Patel, Shivani; Harding, Jessica
Abstract: BACKGROUND AND AIMS: Geographic and neighborhood-level factors such as poverty and education have been associated with an increased risk for incident end-stage kidney disease (ESKD), likelihood of receiving pre-ESKD care, and likelihood of receiving a transplant. However, few studies have examined whether these same factors are associated with ESKD mortality. In this study, we examined county-level variation in ESKD mortality and identified county-level characteristics associated with this variation. METHOD: We identified 1 516 507 individuals (aged 18–84) initiating renal replacement therapy (dialysis or transplant) between 2010 and 2018 using the United States Renal Data System. Among 2807 counties, we estimated county-level all-cause age-standardized mortality rates (ASMR) among patients with ESKD. We then identified county-level demographic (e.g. percentage of female), socioeconomic (e.g. percentage of unemployed), health care (e.g. percentage of without health insurance) and health behavior (e.g. percentage of current smokers) characteristics associated with ASMR using multivariable hierarchical linear mixed models and quantified the percentage of ASMR variation explained by county-level characteristics. RESULTS: County-level ESKD ASMR ranged from 45 to 1022/1000 person-years (PY) (mean, 119/1000 PY). ASMRs were highest in counties located in the Tennessee Valley and Appalachia regions, and lowest in counties located in New England, Pacific Northwest and southern California (Figure 1 ). In fully adjusted models, county-level characteristics significantly associated with higher ESKD mortality included a lower percentage of Black residents (−5.67/1000 PY), lower median income (−5.53/1000 PY), lower number of dialysis facilities/population (−2.25/1000 PY) and higher health care expenditures (5.36/1000 PY). Overall, county-level characteristics explained 16.9% of variation in ESKD mortality. CONCLUSION: Counties with high ESKD-related mortality may benefit from targeted and multi-level interventions that combine knowledge from a growing evidence base on the interplay between individual and community-level factors associated with ESKD mortality.